Digital skills for all? From computer literacy to AI skills in online job advertisements - Matteo Sostero; Songül Tolan (European Commission, Joint Research Centre (JRC), 2022)
The digital transition of the economy is widely expected to change the nature of work. This may happen both through creating new digital job profiles, and by digitising existing jobs. As these changes unfold, new digital skills may be needed at the workplace. We track the trends in demand for digital skills across occupations, using data from over 60 million online job advertisements in the United Kingdom over 2012-2020, the longest-running dataset of this type in Europe. Although online job advertisements tend to understate the prevalence of basic digital skills (like computer literacy or office software) compared to representative surveys, they are particularly precise in tracking skills related to emerging digital technologies. We classify over 13,000 different skills required by employers in the data into clusters, through a community-detection algorithm based on the co-occurrence of skills in job advertisements. Among the many different clusters that emerge, we identify several that relate to advanced digital skills in emerging domains, including Artificial Intelligence (AI). These advanced digital skills, despite forming distinct clusters, are evolving and slowly becoming more interconnected with the rest. We also find that digital skills are at the core of some "non-digital" domains, like the administrative and clerical cluster. Advanced digital skills also pay a notable wage premium: skills in the AI & Big Data cluster are associated with about 10.8% higher offered wages, compared to similar advertisements. For skills in the Advanced ICT cluster, the wage premium is about 15.9% and for ICT Support the premium is about 6.3%. Overall, online job advertisements provide a unique view into the emergence of distinct skill profiles, which can ultimately result in new occupations.
Keywords: 330; Digital Transformation; Future of Work; Digital Skills; Artificial Intelligence